Tonga : 2006 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Tonga's economy has become increasingly vulnerable. Fiscal discipline has weakened, undermining macroeconomic stability and external viability. Medium-term prospects have deteriorated. Moreover, there are other serious downside risks to the fiscal outlook. Further monetary tightening in response to the wage settlement and the full flexibility of the exchange rate system are required. A larger and more dynamic private sector offering alternative employment opportunities would facilitate the downsizing of the public sector. There is a need to improve the reliability, coverage, and timeliness of statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet